2003
DOI: 10.1038/sj.npp.1300311
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Genetic Linkage Between a Polymorphism in the Adenosine 2A Receptor and Panic Disorder

Abstract: Data from clinical and behavioral pharmacological studies have implicated adenosine in anxiety behaviors, while genetic studies have suggested that adenosine receptors may be associated with panic disorder. We have undertaken an analysis of several DNA sequence variations in the adenosine 2A receptor (ADORA2A) in a large sample of panic disorder pedigrees. Individuals from 70 panic disorder pedigrees, and 83 child-parent 'trios', were genotyped at five single-nucleotide polymorphisms (SNPs) in and near the ADO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 48 publications
4
79
2
1
Order By: Relevance
“…Deckert et al (1998) found that PD patients had a higher prevalence of the 1976 T allele compared to controls. Hamilton et al (2004) also report an association between this locus and susceptibility to PD. Therefore, our data suggest that responses to 150 mg caffeine might be examined further to investigate A 2A receptor-mediated mechanisms of anxiety.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Deckert et al (1998) found that PD patients had a higher prevalence of the 1976 T allele compared to controls. Hamilton et al (2004) also report an association between this locus and susceptibility to PD. Therefore, our data suggest that responses to 150 mg caffeine might be examined further to investigate A 2A receptor-mediated mechanisms of anxiety.…”
Section: Discussionmentioning
confidence: 80%
“…In this study, individuals with the T/T genotype of the ADORA2A SNP rs5751876 (1976C/T) reported greater anxiety after 150 mg caffeine compared to other genotypic groups. The same polymorphism has been linked to panic disorder (PD) (Deckert et al, 1998;Hamilton et al, 2004), suggesting that this variant confers a risk for anxiety states in general. Recently, we have also reported that individuals with the 1976T/T genotype also experience more anxiety after acute doses of the prototypic stimulant drug, D-amphetamine (Hohoff et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the nucleoside system is expected to be a target for new drugs to treat mood disorders ) . Caffeine, a competitive antagonist of the A 1 and A 2A Rs (Fredholm et al 1999 ) , promotes anxious behavior both in animal models and humans (Klein et al 1991 ) , and A 2A R polymorphisms are associated with increased incidence of panic disorder and depression (Hamilton et al 2004 ;Lam et al 2005 ;Tsai et al 2006 ) . In addition, mice lacking A 1 or A 2A Rs demonstrate anxiogenic-like behaviors (Gimenez-Llort et al 2002 ;Johansson et al 2001 ;Ledent et al 1997 ) .…”
Section: Mood Disordersmentioning
confidence: 99%
“…Interestingly, the acute administration of caffeine disrupts fear memory (Corodimas et al, 2000) and A 2A R polymorphisms are associated with panic disorders (Deckert et al, 1998;Hamilton et al, 2004), but it is unknown whether A 2A Rs control fear memory and synaptic plasticity in amygdala circuits. Thus, we now explored the involvement of A 2A Rs in the control of synaptic plasticity in the amygdala and their possible role in the control of fear memory.…”
Section: Introductionmentioning
confidence: 99%